2015
DOI: 10.1016/j.jmii.2014.08.025
|View full text |Cite
|
Sign up to set email alerts
|

Multidrug-resistant Acinetobacter baumannii infection among neonates in a neonatal intensive care unit at a medical center in central Taiwan

Abstract: MDRAB infection is responsible for a high mortality rate among neonates in the NICU, especially in those who have neutropenia or thrombocytopenia. Infection control and appropriateness of the initial antimicrobial agent with colistin play an important role in reducing mortality.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
37
0
2

Year Published

2016
2016
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(39 citation statements)
references
References 29 publications
0
37
0
2
Order By: Relevance
“…[5] Studies from India and other parts of the world have reported prematurity, low birth weight ,mechanical ventilation, presence of prolonged intravenous access(central or peripheral), infection with MDR within 7 days of admission, prior exposure to third generation cephalosporins and delay in starting appropriate antibiotics as significant risk factors associated with mortality. [2,4,5,7,[10][11][12]15] In our study 69.2% of babies were preterm (≤30wk) with birth weight ≤1500gm, all had respiratory distress and were ventilated (100%), 53.84% acquired MDR Acinetobacter within 3 days after birth, there was prior use of cephalosporins in 61.5% cases, inappropriate use of antibiotics in 4 case and delay in 7cases. Study from Karachi described mortality due to neonatal Acinetobacter sepsis in 47% and 70% of them died within 4 days of acquiring infection.…”
Section: Discussionmentioning
confidence: 51%
See 3 more Smart Citations
“…[5] Studies from India and other parts of the world have reported prematurity, low birth weight ,mechanical ventilation, presence of prolonged intravenous access(central or peripheral), infection with MDR within 7 days of admission, prior exposure to third generation cephalosporins and delay in starting appropriate antibiotics as significant risk factors associated with mortality. [2,4,5,7,[10][11][12]15] In our study 69.2% of babies were preterm (≤30wk) with birth weight ≤1500gm, all had respiratory distress and were ventilated (100%), 53.84% acquired MDR Acinetobacter within 3 days after birth, there was prior use of cephalosporins in 61.5% cases, inappropriate use of antibiotics in 4 case and delay in 7cases. Study from Karachi described mortality due to neonatal Acinetobacter sepsis in 47% and 70% of them died within 4 days of acquiring infection.…”
Section: Discussionmentioning
confidence: 51%
“…These findings are similar to other studies from India and abroad. [2,4,5,8,10,[12][13][14][15][16][17] All the isolates in our study were MDRAB (100%).The details of the resistance are displayed in [ Table 4]. Testing for colistin and Polymyxin B was not done.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Sebuah penelitian yang dilakukan di Taiwan menunjukkan hasil bahwa penundaan penggunaan antibiotik yang tepat pada pasien dengan multiple drug resistant Acinetobacter baumanii menjadi salah satu faktor yang dapat meningkatkan risiko kematian bayi di NICU. 9 Selain berdampak pada peningkatan risiko terjadinya kegagalan terapi, salah satu dampak yang perlu diwaspadai adalah potensi terjadinya resistensi ketika antibiotik yang diberikan tidak dapat mencapai kadar minimum untuk menghambat pertumbuhan atau membunuh bakteri. Fenomena resistensi antibiotik merupakan salah satu permasalahan yang banyak dialami di NICU.…”
Section: Pendahuluanunclassified